A synopsis of the Brazilian Eucharitidae (Hymenoptera: Chalcidoidea) fauna: an annotated checklist of the family in the country, with a revised key for the New World genera - Silva, Thiago S. R.; Silva-Freitas, Juliana M.; Schoeninger, Karine (Zootaxa, 2019)
The current work provides a revised and updated key to the genera of Eucharitidae occurring in the New World, with the major traits of genera illustrated through high-resolution photomicrography. We provide an annotated list of genera and species currently known from Brazil, with a new record for a genus previously unknown for the country. Additionally, we provide a literature revision of the biology and cuticular hydrocarbon profile for the Eucharitidae. The lack of knowledge on the eucharitid Brazilian fauna is briefly discussed.